Experiences of menopause by women in Zambia - Chibuye, Clifford; Fungwe, Bridget; Tembo, Victoria; Shilengwe, Charity (Lusaka: University of Zambia , School of Medicine, 2013)
The purpose of the study was to explore the eperiences of menopause among zambian women in four provinces; Lusaka, Copperbelt, Luapula and Eastern provinces. The sites for the study were; Katete, Luanshya, Nchelenge and Lusaka. The objectives of the study were achieved and the researchers rejected the hypothesis whi states that "there is a no relationship between knowledge on menopause and coping startegies among menopausal women."
A study submitted in partial fullfilment of the requirements for the award of a Bachelor of Science Degree in Nursing.
Includes bibliographical references.
Keywords: Menopause; Women--Health and hygiene--Sociological aspects